Design and simulation of control systems for a field survey mobile robot platform - Shamshiri, Ramin; Wan Ismail, Wan Ishak; Mohd Kassim, Muhamad Saufi (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Agricultural mobile robots involve automatic and accurate control of different moving parts such as wheel speed and steering. The design challenges of a control system in this regard are the response overshoot, shorter settling time and smaller steady state error. Three controllers, including lead-lag compensator, proportional-integral-derivative (PID) and fuzzy logic controller were designed and simulated in this study to control the angular rate of the shaft of a DC motor actuator for a field survey mobile robot that moves between plants rows to perform image acquisition task through a digital camera mounted on a two link arm attached on the robot base. The response of the actuator model for each controller were determined and compared for a sinusoidal and a step input that simulated robot speed and positioning references respectively. Performance analysis showed the effectiveness of the PID and lead-lag compensator response for the wheel steering task, while the fuzzy logic controller design had a better performance in wheel speed control. The output of this analysis was a proved satisfaction of the proposed design criteria which results enhanced mobility of the robot in terms of fast response, speed control accuracy and smooth steering at row-end turnings.